Pelatihan Pengembangan Karir dan Literasi Digital Keuangan bagi Atlet Disabilitas Kabupaten Ciamis - Yanti, Rini Agustin Eka; Maryati, Sri; Herlina, Nina (Unri Conference Series: Community Engagement, 2024)
The problems experienced by people with disabilities include difficulty meeting their basic personal needs, difficulty finding work, health problems, and limited education. The implementation method was carried out in Community Service through the Community Partnership Program to empower disabled athletes under the guidance of NPCI Kab. Ciamis is carried out using discussion, training, and mentoring methods carried out in several stages. Based on the activities carried out, it is hoped that disabled athletes in Kab. Ciamis will have the understanding to manage their careers in sports as well as possible by providing career options, for example by opening up career opportunities in the field of entrepreneurship. Increasing knowledge about other career opportunities that can be obtained by people with disabilities or other careers that have greater opportunities in the economic field without ignoring their role as an outstanding athlete. It will also strengthen aspects of the financial independence of athletes with disabilities under the guidance of NPCI Kab. Ciamis.